THE IMPACT OF CHRONIC DISEASES IN INDIA: AN ANALYSIS OF HEALTH SYSTEM RESPONSES - Allama Zaki Almubarok; Evans Dennison. J. (JTH: Journal of Technology and Health, 2025)
Chronic diseases, particularly cardiovascular diseases, diabetes, and hypertension, have become significant public health challenges globally, with India experiencing an increasing burden. The prevalence of these non-communicable diseases (NCDs) is influenced by rapid urbanization, lifestyle changes, and socio-economic disparities. In urban areas, 25% of the population is affected by hypertension, with a marked increase in lifestyle-related diseases due to poor dietary habits, physical inactivity, and stress (Gupta et al., 2023). In contrast, rural areas show a higher prevalence of diabetes, with approximately 18% of rural populations diagnosed, mainly due to underdiagnosis and inadequate healthcare access. This study employs a mixed-methods approach, combining quantitative surveys with 500 participants and qualitative interviews with 30 healthcare professionals, to examine the prevalence, management challenges, and socio-economic factors affecting chronic disease outcomes in urban and rural India. The study finds that 40% of healthcare professionals in rural areas report inadequate training in chronic disease management. Additionally, 60% of rural patients face significant barriers to accessing care. The findings suggest that targeted interventions are needed, with a focus on improving healthcare professional training, resource allocation, and raising awareness in underserved regions. This research provides valuable insights into the healthcare challenges and potential solutions for managing chronic diseases in India.